Comprehensive Approach to Heart Failure: an Urgent Need - Yanier Coll Muñoz (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
Heart failure leads to the activation of a neurohormonal response that interacts with the hemodynamic changes, which are joined by functional and structural myocardial abnormalities, that may exist. This paper addresses the role of the renin-angiotensin system in the pathophysiology of heart failure and the use of non-invasive complementary methods that provide additional information necessary for the assessment and comprehensive management of patients, without losing the essential connection between the doctor and the patient.